FILIAL PIETY DISCREPANCY AND MENTAL HEALTH OF IMMIGRANT CHINESE OLDER ADULTS IN THE UNITED STATES. (11th November 2018) - Xu, L; Guo, M; Liu, J; Mao, W; Chi, I
Abstract: This study aims to investigate the association between six domains of filial discrepancy and mental health outcomes. Data were derived from the Population Study of Chinese Elderly, an epidemiological study of Chinese aged 60 and older in Chicago. Mental health was measured by anxiety and stress. Filial discrepancy was calculated by filial receipt minus expectations in six domains (respect, care, greet, bringing happiness, obedience, and financial support. Negative Binominal Regressions were performed. Results showed that positive filial discrepancy in respect and negative filial discrepancy in respect or financial support were significantly associated with anxiety. Positive discrepancy in "greet" or "financial support" and negative discrepancy in "respect", "greet", "obedience", or "financial support" were significantly correlated with stress. This study showed that negative filial discrepancy played more important roles than positive ones and each dimension of filial discrepancy functioned differently in the mental health outcomes of older parents in Chinese immigrant family.